2014
DOI: 10.1007/978-3-642-54215-2_16
|View full text |Cite
|
Sign up to set email alerts
|

Trpm2

Abstract: TRPM2 is the second member of the transient receptor potential melastatin-related (TRPM) family of cation channels. The protein is widely expressed including in the brain, immune system, endocrine cells, and endothelia. It embodies both ion channel functionality and enzymatic ADP-ribose (ADPr) hydrolase activity. TRPM2 is a Ca(2+)-permeable nonselective cation channel embedded in the plasma membrane and/or lysosomal compartments that is primarily activated in a synergistic fashion by intracellular ADP-ribose (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
62
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(63 citation statements)
references
References 148 publications
1
62
0
Order By: Relevance
“…Involvements of the comparable aspartate and glutamate of TRPM5 in its activation by Ca 2ϩ should be addressed. TRPM2 is activated in a synergistic fashion by intracellular ADP-ribose and Ca 2ϩ (48). It has been reported that the mutation of the calmodulinbinding domain, located in the N terminus of TRPM2, made the channel nonfunctional (49).…”
Section: Discussionmentioning
confidence: 99%
“…Involvements of the comparable aspartate and glutamate of TRPM5 in its activation by Ca 2ϩ should be addressed. TRPM2 is activated in a synergistic fashion by intracellular ADP-ribose and Ca 2ϩ (48). It has been reported that the mutation of the calmodulinbinding domain, located in the N terminus of TRPM2, made the channel nonfunctional (49).…”
Section: Discussionmentioning
confidence: 99%
“…The second member of this subfamily to be cloned, TRPM2, is a 1503-amino acid channel permeable to Ca 2ϩ , Na ϩ , and K ϩ (6) and is widely expressed in many cell types including brain, hematopoietic cells, heart, and endothelial cells (7,8). Its role in normal physiological conditions as well as in oxidative stress is under investigation in many cell types (9). Oxidative stress, TNF␣, and amyloid ␤-peptide are among the key extracellular signals known to activate TRPM2 (10 -13).…”
Section: Transient Receptor Potential (Trp)mentioning
confidence: 99%
“…TRPM2 channels are permeable to Ca 2ϩ , Na ϩ , and K ϩ and are widely expressed in many cell types including brain, hema-topoietic cells, heart, vascular smooth muscle, and endothelial cells (7,8). The role of TRPM2 in numerous cell types including brain, heart, endothelial cells, and inflammatory cells under physiological conditions as well as oxidative stress is actively being investigated (9). Extracellular signals that activate TRPM2 include oxidative stress, TNF␣, and amyloid ␤-peptide (10 -13).…”
Section: Transient Receptor Potential (Trp)mentioning
confidence: 99%